Design with operational amplifiers and analog integrated circuits - Franco, Sergio (McGraw Hill, 2002)
Intended for a design-oriented course in applications with operational amplifiers and analog ICs. This title also serves as a reference for practicing engineers, and includes pedagogy (additional problems, coverage of negative feedback, and effective layout), technology (folded-cascode amplifiers, and low-voltage amplifiers), and more.